1995
DOI: 10.1080/01635589509514413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of timing and duration of dietary conjugated linoleic acid on mammary cancer prevention

Abstract: Conjugated linoleic acid (CLA) is a minor fatty acid found predominantly in the form of triglycerides in beef and dairy products. Previous work by Ip and co-workers showed that free fatty acid-CLA at < or = 1% in the diet is protective against mammary carcinogenesis in rats. The present study verified that the anticancer activities of free fatty acid-CLA and triglyceride-CLA are essentially identical. This is an important finding, because it rules out a nonspecific free fatty acid effect. In terms of practical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1
10

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(82 citation statements)
references
References 11 publications
2
69
1
10
Order By: Relevance
“…Both preparations increased the incorporation of total CLA in PBMC by $ 35%. Moreover, the two studies that directly compared effects of CLA given as fatty acids and as glycerides found essentially identical effects on mammary cancer prevention (Ip et al, 1995) and body composition (Rahman et al, 2001). Recently, we also obtained identical effects on body composition when feeding mice CLA 50:50 either as free fatty acid or as glycerides (unpublished data).…”
Section: Discussionmentioning
confidence: 50%
“…Both preparations increased the incorporation of total CLA in PBMC by $ 35%. Moreover, the two studies that directly compared effects of CLA given as fatty acids and as glycerides found essentially identical effects on mammary cancer prevention (Ip et al, 1995) and body composition (Rahman et al, 2001). Recently, we also obtained identical effects on body composition when feeding mice CLA 50:50 either as free fatty acid or as glycerides (unpublished data).…”
Section: Discussionmentioning
confidence: 50%
“…Twenty-four healthy subjects (12 men and 12 women) aged 22.3 Ϯ 0.3 y old with a mean body mass index of 20.2 Ϯ 0.4 kg/m 2 were randomly assigned to a CLA-treated group (6 men and 6 women) or a control group (6 men and 6 women). All subjects were generally healthy, as demonstrated by their medical history and a physical examination.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these fats, such as CLA (conjugated linoleic acid), could be beneicial to human health. CLA is important in the prevention of speciic cancers and in the treatment of obesity, immune functions, and potential beneicial efects on coronary heart disease [8].…”
Section: Faty Acid Composition Inluencing Human Health and Meat Qualitymentioning
confidence: 99%
“…CLA has favorable efects on human health, increasing immunostimulatory, antimutagenic, and antioxidant activity [8]. In addition, polyunsaturated faty acids (PUFAs) present in bovine fat such as linoleic (C18: 2n−6) and linolenic (C18: 3n−3) and monounsaturated faty acids (AGMI), such as oleic acid (C18: 1, n−9), which ofer protection to the cardiovascular system, since balanced consumption of these drugs is associated with a reduction in serum cholesterol levels and an increase in high-density lipoprotein (HDL) [9].…”
Section: Introductionmentioning
confidence: 99%